Exploration of Technology Transformation-Based Learning Experiences and Higher Education Leadership - Muh Tang S; Zulkifli Zulkifli; B.M.A.S. Anaconda Bangkara; Maryam Maryam; Dina Hajja Ristianti (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
An overview of the management of technology-based higher education and digital applications in an era that is now increasingly developing is becoming a critical study. For this reason, we conducted several interviews with more of the supervisors at Bontang University. Then we also believe in studying some of the scientific evidence that has raised technology-based education in tertiary institutions, which we then examine by involving various techniques such as data coding, and in-depth data interpretation to get answers as valid and reliable study findings. After going through a series of discussions and reviewing the results of interviews and other scientific evidence, it can be concluded that a review of technology-based education governance is a critical study considering that there are still many universities that have not fully opened their doors to technology-based teaching for management reasons and other limitations. These findings will be valuable insights for developing similar research in the future.